Morphotectonic positions and paleoseismic characteristics of basin faults on Karakova horst near Celtikci (Denizli-Turkey) - Hancer, Mete; Akyol, Erdal (IJRDO-Journal of Applied Science, 2018)
Denizli graben, which is one of the active graben structures of Western Anatolia, is a seismically active region. The Karakova horst is located in the middle of this graben. Recently, the earthquake epicenters have intensified on the Kaleköy-Uzerlik fault line that forms the two wings of the horst. In this study, geological, morphological and geophysical studies were carried out in order to determine the antithetic and synthetic of these faults. A fault belonging to the early graben phase and without any trace on the surface was observed. It was buried by the Neogene sediments while the others were covered by Quaternary sediments. Therefore, they were interpreted as paleosismologically possible active faults. These faults occur as a result of opening in NE-SW direction. They can be catastrophic for the buildings and have to be taken into account for microzoning studies.